Islamic Theology and Sustainable Peace: The case of Darunnajah Islamic Boarding School - Darojat, Much Hasan; Izfanna, Duna; Artalim, Muntaha; Ogunbado, Ahamad Faoisy (Madania: Jurnal Kajian Keislaman, 2025)
This article aims to explore the role of Darunnajah Islamic Boarding School in building sustainable peace based on Islamic theology. The theological approach chosen is Ahlusunnah wal Jamaah in Asy‘ariyyah formulation. This belief applies a moderate attitude and keeps people away from judgmental or disbelieving attitudes. This research uses a qualitative approach, combining interviews and document analysis of Darunnajah’s peace education programs, including international language and cultural collaborations and data from official reports and the institution’s website. Theological concepts are analyzed using authoritative primary and secondary references to explain how Pesantren, as an Islamic educational institution, integrates Islamic values with local wisdom to shape students’ character and promote peace. The results show that Darunnajah applies a holistic approach involving character education, foreign language skills, and classical Arabic book literacy. It also fosters awareness of global peace and cross-cultural understanding while maintaining Islamic identity. This study concludes that Darunnajah’s integration of Islamic theology as the foundation of peace education can serve as a model for sustainable peacebuilding. Artikel ini bertujuan untuk mengeksplorasi peran Pondok Pesantren Darunnajah dalam membangun perdamaian berkelanjutan berbasis teologi Islam. Pendekatan teologis yang dipilih adalah Ahlusunnah wal Jamaah dalam formulasi Asy‘ariyyah. Akidah ini menerapkan sikap moderat dengan menjauhkan umat dari sikap menghakimi atau mengkafirkan tindakan seseorang. Penelitian ini menggunakan pendekatan kualitatif melalui wawancara dan analisis dokumen, mencakup program pendidikan perdamaian Darunnajah yang bekerja sama secara internasional dalam bidang bahasa dan budaya, serta data dari laporan resmi dan situs web lembaga.  Konsep teologis dianalisis melalui referensi primer dan sekunder yang otoritatif untuk menjelaskan bagaimana pesantren, sebagai lembaga pendidikan Islam, mengintegrasikan nilai-nilai keislaman dengan kearifan lokal dalam membentuk karakter santri dan membangun perdamaian. Hasilnya menunjukkan bahwa Darunnajah menerapkan pendekatan holistik yang mencakup pendidikan karakter, keterampilan bahasa asing, dan literasi kitab klasik. Pesantren ini juga menumbuhkan kesadaran akan perdamaian global dan pemahaman lintas budaya, sekaligus menjaga identitas keislaman. Studi ini menyimpulkan bahwa integrasi teologi Islam sebagai dasar pendidikan perdamaian dapat menjadi model bagi pembangunan perdamaian yang berkelanjutan.